2011
DOI: 10.1007/s12678-011-0067-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Growth of Surface Oxides on Nickel. Part 1: Formation of α-Ni(OH)2 in Relation to the Polarization Potential, Polarization Time, and Temperature

Abstract: Electro-oxidation of Ni(poly) in 0.5 M aqueous KOH solution at various polarization potentials (E p ) up to 0.5 V vs. reversible hydrogen electrode, for polarization times (t p ) up to 2 h, and at 285≤T≤318 K leads to the formation of a thin layer of α-Ni(OH) 2 . Interfacial capacitance measurements show that the Ni(poly) electrode covered with a layer of α-Ni(OH) 2 can be completely reduced back to its metallic state by applying a negativegoing potential scan with a lower potential limit of −0.2 V. An increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 91 publications
(170 reference statements)
7
114
1
1
Order By: Relevance
“…These findings are in very good agreement with those presented by Barbosa et al [5], Motheo et al [17] and by Kim and Park [18]. It should be stressed however that comprehensive studies of Ni oxide growth and characterization were published in important papers by van Drunen et al [22] and by Alsabet et al [39][40][41].…”
Section: Methodssupporting
confidence: 90%
“…These findings are in very good agreement with those presented by Barbosa et al [5], Motheo et al [17] and by Kim and Park [18]. It should be stressed however that comprehensive studies of Ni oxide growth and characterization were published in important papers by van Drunen et al [22] and by Alsabet et al [39][40][41].…”
Section: Methodssupporting
confidence: 90%
“…It has been suggested that the electrochemically formed α-Ni(OH) 2 surface component has a limiting thickness of two layers. 19 The adsorbed oxalate layer may therefore have a similar thickness of about two layers or less. Conventional IR reflectance measurements are incapable of detecting such thin surface components.…”
Section: Resultsmentioning
confidence: 99%
“…Ni(OH) 2 also forms electrochemically on Ni electrodes in alkaline media, which has importance for the development of Ni-based electrocatalysts [23,105,179,[184][185][186][187]. Consequently, the surface electrochemistry has been extensively studied using atomic force microscopy [188], ellipsometry [181,[189][190][191], IR spectroscopy [192], Raman spectroscopy [166,193,194], UV-Vis spectroscopy [192,195], voltammetry [179,185,[196][197][198][199][200][201], X-ray scattering [176], XPS [179,202] and gravimetry with an electrochemical quartz crystal microbalance [203,204]. During a forward voltammetric sweep, a surface bilayer of α-Ni(OH) 2 underlaid by NiO x forms initially [179].…”
Section: (D) Chemical Ageingmentioning
confidence: 99%
“…The voltammetric peak at approximately 0.3 V versus RHE has been used to estimate the surface area of nickel electrodes [197]. The method approximates that the peak corresponds to the formation of a monolayer consisting entirely of α-Ni(OH) 2 .…”
Section: (D) Chemical Ageingmentioning
confidence: 99%